2010
DOI: 10.1111/j.1440-1681.2009.05325.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of amiloride on the current mediated by native GABAA receptors in cultured neurons of rat inferior colliculus

Abstract: 1. The diuretic amiloride is known to modulate the activity of several types of ion channels and membrane receptors in addition to its inhibitory effects on many ion transport systems. However, the effects of amiloride on some important ion channels and receptors, such as GABA(A) receptors, in the central nervous system have not been characterized. 2. In the present study, we investigated the functional action of amiloride on native GABA(A) receptors in cultured neurons of rat inferior colliculus using whole-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…3B). We repeated the behavioural tests with the Na/H exchange inhibitor amiloride, because amiloride penetration across the blood–brain barrier is known to be poor (Sipos and Brem, 2000; Fisher, 2002; Liu et al , 2010). Notably, the effects of amiloride and MIA were similar (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3B). We repeated the behavioural tests with the Na/H exchange inhibitor amiloride, because amiloride penetration across the blood–brain barrier is known to be poor (Sipos and Brem, 2000; Fisher, 2002; Liu et al , 2010). Notably, the effects of amiloride and MIA were similar (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is based on (i) the post-asphyxia increase and alkaline overshoot of both brain intracellular pH and extracellular pH, which indicates a net loss of acid equivalents from brain tissue; (ii) direct measurements of the extracellular pH levels and dynamics in the brain and the rest of the body, which indicated a strict compartmentalization of brain extracellular pH by the blood–brain barrier under normal conditions and in response to asphyxia in the Day 6 rats; (iii) the specific block of the post-asphyxia brain alkalosis by MIA, an inhibitor of Na/H exchange (Kendall et al , 2006; Pedersen et al , 2006) and (iv) the equally strong inhibitory action on seizures by MIA and amiloride, whereof the latter is an Na/H exchange inhibitor that has a very low permeability across the blood–brain barrier (Sipos and Brem, 2000; Fisher, 2002; Liu et al , 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be ruled out that the action of diminazene aceturate on GABAergic transmission under conditions of our experiments is determined by the action of this drug precisely on the above-mentioned proton-activated channels that are coupled, in some a way, with GABA-activated ones. Such an assumption is indirectly confirmed by the fact that amyloride, another blocker of protonactivated channels, influences considerably the effects induced by application of exogenous GABA [6,7] and GABA-mediated PSCs [8]. Recently, it was found that functional interaction between GABA A receptors and ASIC1a channels is quite possible; a protein complex including both abovementioned receptors has been identified [9].…”
Section: Resultsmentioning
confidence: 82%
“…Amiloride, the prototypical acid-sensing ion channel (ASIC) antagonist, acts as a competitive antagonist for the heteromeric GABA-A abg receptors (Inomata et al, 1988;Fisher, 2002;Liu et al, 2010). The activity of amiloride on the GABA-A r1 receptor remains unclear.…”
Section: Resultsmentioning
confidence: 99%